Revitalizing Math Education: Unveiling the Impact of Holistic Mathematics Education Based “Sistem Among” in Elementary Classrooms - Rahmatul Hayati; Asmayanti -; Wahyu Prima (AL-ISHLAH: Jurnal Pendidikan, 2024)
This research examines the impact of the Holistic Mathematics Education (HME) model based on the Among system on the mathematical concept understanding of third grade students at SD Negeri 21 Pulau Punjung. This model holds significant relevance to the current paradigm of liberating learning. In the era of modern education, there is a strong emphasis on learning approaches that promote independence, creativity, and critical thinking among students. The implementation of this model has shown an increase in mathematical concept understanding, as evidenced by statistical analysis (significance level 0.001). Based on the analysis results, it can be proven that the HME model based on the "among" system has a positive impact on the mathematical concept understanding of third-grade students at SDN 21 Pulau Punjung. The success of this method in enhancing mathematical concept understanding underscores the urgency to integrate more innovative and inclusive approaches in the mathematics curriculum, especially at the elementary level, as liberating education focuses not only on academic knowledge but also on the development of students' competencies and character. This study provides empirical evidence of the importance of adopting a more holistic and interactive educational model in elementary schools. Consequently, these findings support a transition towards more responsive, participatory, and future-ready learning methods.